European Freight Transport 2030 - Jespersen, Per Nomann; Nielsen, Lise Drewes (Proceedings from the Annual Transport Conference at Aalborg University, 2004)
In a future workshop setting, 30 transport experts in the course of one day produced a scenario for the European freight sector in 2030, and a line of events leading to this scenario. The scenario describes transport technology, ICT, and transport infrastructure development, as well as the societal and regulatory framework conditions for this development. The paper presents these results, as well as the methods use for producing them – a future workshop with phases of critique, utopian visions and realisation. The paper discusses the validity of scenarios produced by this method, and compares to other types of scenario production methods.